Assessment of cytotoxic activity of water from various water supply sources - Verholias, M.R.; Trakhtenberg, I.M.; Dmytrukha, N.N. (Environment & Health, 2016)
Objective. We assessed a quality of drinking water from various sources of water supply by its cytotoxic effect on the cultures of human and animal cells in the experiments in vitro.Materials and methods. We investigated a cytotoxic effect of control water, obtained according to the requirements of the State Standards of Ukraine 4174: 2003 in the Laboratory of the Institute of Colloid Chemistry and Water Chemistry, National Academy of Sciences of Ukraine, tap water, pump-room water, and bottled water "Znamenska." Studies were performed on the cells of HEK-293 line (human kidney cells), L929 line (mouse fibroblasts), and RTR (piglet testicles cells) from Zabolotny D.K. Institute of Microbiology and Virology, National Academy of Sciences of Ukraine.Results. Research of cytotoxicity of mentioned water samples in the MTT-test showed that the most toxic activity against human kidney cells (HEK-293) was manifested by the pump room water and tap water (a number of viable cells under their effect made up 64.41% and 77.00% respectively). In "Znamenska" water a number of viable cells made up 81.75%, control water demonstrated the smallest impact -91.73%. In the test with sulforodamin B a number of living cells under exposure of control water made up 103.00%, of tap water - 82.45%, of water from the pump rooms - 89.20%, of "Znamenska" water - 96.75%. In the test with sulforodamin B after addition of control water a number of viable cells was 81.45%, after addition of "Znamenska" water - 69.45%, tap water - 68.2%, and water from the pump room - 66 95%.Conclusions. Tap water had the highest cytotoxic effect according to MTT-test and test with sulforodamin B on human kidney cells (HEK-293), water from the pump room had the highest effect on the mouse fibroblast (L 929), water from the pump room had the highest one on the RTR testicles of piglets. Control water had the smallest impact on the cell viability. A negative impact of water on cell viability was manifested in the violations of mitochondria function and protein synthesis. The cells of RTR line were more sensitive to the toxic effect of water that may indicate the possible negative impact of water on the reproductive system of the organism.
Keywords: cytotoxicity; cell culture; drinking water